The Meeting of Religions in the Modern World: Opportunities and Dangers - Nandhikkara, Jose; Macquarrie, John (Journal of Dharma, 1975)
For thousands of years the several cultures of mankind and the religions belonging to them went their ways in relative isolation. To be sure, there was always some coming and going, and we are constantly surprised to discover how even in the most remote times of antiquity the migrations of peoples and the adventurous voyages of traders led to the dissemination of ideas far beyond their native regions. But in general it would be true to say that mankind was divided into fairly homogenous cultural and religious blocks, each concentrated in a particular region of the earth’s surface. Some historians have been so impressed with these divisions that they have maintained that (at least, until very recently) there has been no unitary world history but rather a collection of histories, each of them self-contained and carrying within itself the springs of its own development, flowering and eventual decline. A notable advocate of this point of view was Oswald Spengler, and it is interesting to note how he regards each culture as determined in all its aspects by certain basic world-conceptions that ate essentially religious in character. More recently, Arnold Toynbee has also argued the case for viewing the past of mankind as a plurality of histories, each relatively independent. His scheme is even more elaborate than Spengler’s, and recognizes more than a score of cultures or civilizations.